NEW DATA ON FIRST ATTEMPTS TO CODIFY LAW IN THE PRINCIPALITY OF SERBIA (1827–1837) - Drakić, Gordana; Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The article reveals new data on first attempts of codification of civil law in the Prinipality of Serbia. The attempts lasted from 1827, the year in which prime codification works are recorded, to 1837, when French Civil Code was rejected as a role model of future Serbian code. The revelations came from archive materials and non-Serbian literature and press. They are related to the work of the first and second codification committee, draft civil code composed between 1834 and 1837 and some details regarding the engagement of expert lawyers for the purpose of drawing up civil code.